(-2, 0), (2, 0), and (3, 0)
:)
Step-by-step explanation:
f(n) = - 29 - f( n - 1 )
f(1) = - 16
Now
f(2) = - 29 - f ( 2 - 1 )
= - 29 - f ( 1)
= -29 - ( - 16)
= - 29 + 16
= - 13
7. YZ
8. 27,49
9. 51
10.c
11. b
The friend would be incorrect. The antelope running 60 feet per second will be safe if the cheetah running at 90 feet per second is 650 feet behind it. To prove this, we can calculate the time it takes for the cheetah to reach the initial position of the antelope which is 650 ft from its initial position. We do as follows:
time to reach 650 ft = 650 ft / 90 ft/s = 7.22 s
After 7.22 s, the antelope would be,
distance of the antelope = 60 ft /s (7.22 s) = 433.33 ft
It would be 433.33 ft away from its initial position. So, the cheetah would not be able to reach the antelope when it travels 650 ft.